ROLE OF INTERLEUKIN-1 IN PATHOGENESIS OF RADICULAR CYST - Qureshi, Waqar ur Rehman; Asif, Muhammad; Qari, Iftikhar Hossein; Qazi, Javed Akhtar (Journal of Ayub Medical College Abbottabad, 2010)
Background: Interleukin-1 (IL-1) is one of the cytokines produced by macrophages, monocytes and dentritc cells. Macrophages are present in apical granuloma and the wall of the radicular cyst. This cytokine causes the cyst expansion and is involved in proliferation of fibroblasts in the cyst wall and stimulate the fibroblasts to produce more prostaglandin. Radicular cyst is the most common cyst of the jaws which is usually associated with necrotic pulp of the tooth. The cyst formation requires proliferation of the epithelial rest cells of Malassez present in the periodontal ligament. Proliferation of epithelial rest cells of Malassez is an essential event in the Pathogenesis of radicular cyst. Objective of the study was to investigate the effect of IL-1 on epithelial cell proliferation which is an important factor in the pathogenesis of radicular cyst. Methods: The cyst walls of 20 radicular cysts were removed and were cultured in vitro to grow the epithelial cells. The culture were rapidly contaminated and dominated by growth of fibroblasts. Therefore another cell line was used for the experiments. Results: The result showed that proliferation was stimulated with increased in a biphasic manner with maximum stimulation at 1.25 Î·g/ml, beyond this concentration proliferation was decreased. Conclusion: IL-1 had a proliferative effect on epithelial cells at low concentrations which may be playing a role in evoking an inflammatory reaction and stimulating the epithelial cell rests of Malassez to proliferate to form radicular cyst. Keywords: Interleukin-1, radicular cyst, epithelial cell rests of Malassez, Epithelial cell proliferation